Development of Tourist Village Website to Increase Tourism in Lake Toba - Riyanthi Angrainy Sianturi; Yohanssen Pratama; Verawaty Situmorang; Arnaldo M Sinaga (STMIK Budi Darma, 2022)
Currently, the Lake Toba area is included in one of the 10 priority tourism destination locations, so there are challenges to make changes to world tourism trends that utilize digital technology. So that several strategies must be carried out to capture these opportunities, one of which is through digitalization. For this reason, the development of a tourist village website in the Lake Toba area needs to be carried out to be able to take advantage of digital technology as a promotional media. The method applied in developing a tourist village website is the waterfall. The reason for implementing the waterfall method in developing a tourist village website is because all the requirements obtained from the client are clear and there are no more changes in the middle of implementation. The website displays good photography works and is equipped with the concept of story-telling. In addition to obtaining information about tourism in the Lake Toba area, the community can be directly involved as actors in tourism activities. Thus, a website manager will be formed in each tourist village of the Lake Toba Region. From the results of the development, it was found that the community's introduction to tourist villages in Lake Toba is increasing